Pengaruh Konsumsi Rokok Terhadap Hasil Vo2Max Pada Pemain Futsal Putra Hatrick Solo - Chotimah, Chusnul; , Totok Budi Santoso , S.Fis , MPH; , Dwi Kurniawati, SSt.FT (2015)
BACKGROUND: smokingcurrentlybecomes habit both for adult and adolescence. However, although they already know the effect and impact that will be obtained by smoking, even for athlete, this bad behavior conducted by so called smoker, especially for heavy smoker consume more than one pack or 10-20 cigarettes a day. It is inappropriate for athlete, because the physical and sport activity occupied is surely to maintain his health and fitness. RESEARCH OBJECTIVE: this research is to understand the percentage of effect of cigarette consumption toward result of vo2max male futsal player of Hatrick solo. RESEARCH BENEFIT: thiscan be used to understand the capacity of smoker VO2max player and to add knowledge of case in accordance to the condition of smoking athlete. Research method: this research is suing observational with crosssectional approach. The amount of sample used is 50 respondents. The sample choosing is from age of 19 up to 29 years old. Data collection is using questionnaire to understand personal data and behavior and Bleeptest to understand its VO2max capacity. The statistical analysis is using Paired Sample T-test and Kolmogorof as much as 95%. RESEARCH RESULT: based on the statistical analysis result it is obtained that the influence of cigarette consumption toward result of VO2max is with significance (p= 0.000 < 0.05). CONCLUSION: cigarette consumption has a significantly influence toward the capacity of VO2max futsal male club players of Hatrick Solo. KEYWORDS: smoking athlete, cigarette consumption, VO2max capacity